Human umbilical cord mesenchymal stem cells facilitate the up‐regulation of miR‐153‐3p, whereby attenuating MGO‐induced peritoneal fibrosis in rats. Issue 7 (14th April 2018) - Li, Dong; Lu, Zhenyu; Li, Xiyuan; Xu, Zhongwei; Jiang, Jianqing; Zheng, Zhenfeng; Jia, Junya; Lin, Shan; Yan, Tiekun
Abstract: MiRNAs contribute greatly to epithelial to mesenchymal transition (EMT) of peritoneal mesothelial cells (PMCs), which is a crucial step in peritoneal fibrosis (PF). In this study, we tried to profile whether miRNA expression differences exist after human umbilical cord mesenchymal stem cells (hUCMSCs) treatment in PF rats and investigate the possible role of miR‐153‐3p involved in anti‐EMT process. We randomly assigned 34 rats into three groups: control group (Group Control), MGO‐induced PF rats (Group MGO) and hUCMSCs‐treated rats (Group MGO + hUCMSCs). MiRNA microarrays and real‐time PCR analyses were conducted in three groups. α‐SMA, Snail1 and E‐cadherin expression were detected by Western blot. Luciferase reporter assays were used to detect the effects of miR‐153‐3p overexpression on Snai1 in rat peritoneal mesothelial cells (RPMCs). We identified differentially expressed miRNAs related to EMT, in which miR‐153‐3p demonstrated the greatest increase in Group MGO + hUCMSCs. Transient cotransfection of miR‐153‐3p mimics with luciferase expression plasmids resulted in a significant repression of Snai1 3′‐untranslated region luciferase activity in RPMCs. These studies suggest that miR‐153‐3p is a critical molecule in anti‐EMT effects of hUCMSCs in MGO‐induced PF rats. MiR‐153‐3p might exert its beneficial effect through directly targeting Snai1.